Brazil throws Microsoft out of the windows. - Macpherson, Sholto (New Internationalist, 2005)
Reports that Brazil has pledged to invest heavily in its own software industry in a bid to keep pace with the technological advance of the developed nations. Decision to support the open-source software movement; Plan to eliminate all Microsoft Windows operating systems from federal departments; Sergio Amadeu de Silveira, president of the Government's National Institute for Information Technology, as the driving force in the initiative.